Activity and Demands of Catholic Concern for Animals - Smykowski, Krzysztof (Studia Ecologiae et Bioethicae, 2017)
The purpose of this article is to present the activities of an association Catholic Concern for Animals founded in 1929. It is one of the few organizations working for the protection of animals inspired by the teachings of the Catholic Church. Its members engage in various activities on a variety of platforms, including educational campaigns and protests. Publishing work is also important. The association has been publishing a quarterly “The Ark” since 1937, in which it informs readers about its current operations and publishes articles on animals and their welfare. In 2015 the leaders of the organization addressed an appeal to Pope Francis, appealing for a change in the Catechism of the Catholic Church, highlighting the role of a man in service of the natural world and postulating a significant reduction of experimentation on animals. It seems that some of these postulates go too far and are not compatible with an integral vision of man and of the world proclaimed by the Church.